Efficacy and safety of second-line therapy by S-1 combined with sintilimab and anlotinib in pancreatic cancer patients with liver metastasis: a single-arm, phase II clinical trial - Qiu, Xin; Lu, Changchang; Sha, Huizi; Zhu, Yahui; Kong, Weiwei; Tong, Fan; Wang, Qiaoli; Meng, Fanyan; Liu, Baorui; Du, Juan (Frontiers in Immunology, 2024)
Background Pancreatic adenocarcinoma carries a grim prognosis, and there are few recognized effective second-line treatment strategies. We attempted to evaluate the efficacy and safety of a combination of S-1, sintilimab, and anlotinib as a second-line treatment in pancreatic cancer patients with liver metastasis. Methods Pancreatic cancer patients with liver metastases were recruited. S-1 was administered orally at 25 mg/m2 bid, anlotinib was administered orally at 12 mg qd from day 1 to day 14, and sintilimab was administered intravenously at 200 mg on day 1. This method was repeated every 21 days, and the therapeutic effect was evaluated every 3 cycles. The primary outcome was the objective response rate (ORR). Results Overall, 23 patients were enrolled in this study of whom 19 patients had objective efficacy evaluation. The ORR was 10.5% (95% CI 0.4%–25.7%) in the evaluable population. The progression-free survival (PFS) was 3.53 (95% CI 2.50–7.50) months, and the overall survival (mOS) was 8.53 (95% CI 4.97–14.20) months. Grade 3 adverse events were 26.1%, and no grade 4 or above adverse events occurred. High-throughput sequencing was performed on the tumor tissues of 16 patients; patients with HRD-H (n = 10) had shorter PFS than those with HRD-L (n = 6) (2.43 vs. 5.45 months; P = 0.043), but there was no significant difference in OS between the two groups (4.43 vs. 9.35 months; P = 0.11). Conclusions This study suggests the advantage of S-1 combined with sintilimab and anlotinib in extending OS as a second-line therapy in pancreatic cancer patients with liver metastasis. Clinical Trial Registration: ChiCTR2000030659